Pengaksesan maklumat perundangan di Malaysia dan peranan pustakawan - Noordin, Shaikh Mohamed (Persatuan Pustakawan Malaysia, 2005)
Various sources of legal information are available and this variety of sources have tremendoulsy hehaed legal practitioners and law librarian in their quest for legal information. This article looks at the dwerent types of legal resources that are available and its usage. It proposes the setting up of a Pusat Kebangsaan Bagi Maklumat Perundangan Negara and Institut Maklumat Perundangan Malaysia.